2005
DOI: 10.1002/app.21387
|View full text |Cite
|
Sign up to set email alerts
|

Spinning and properties of poly(ethylene terephthalate)/organomontmorillonite nanocomposite fibers

Abstract: By in situ polycondensation, a intercalated poly(ethylene terephthalate)/organomontmorillonite nanocomposite was prepared after montmorillonite (MMT) had been treated with a water-soluble polymer. This nanocomposite was produced to fibers through melt spinning. The resulting nanocomposite fibers were characterized by X-ray diffraction (XRD), differential scanning calorimeter (DSC), and transmission electron microscopy (TEM). The interlayer distance of MMT dispersed in the nanocomposite fibers was further enlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 32 publications
4
43
0
2
Order By: Relevance
“…Modification of clay with the imidazolium ILs results in a shift in the (001) peak by 0. 8 . This corresponds to an increase in d-spacing of about 0.16 nm, indicating that the surfactant molecules are intercalated into the clay galleries.…”
Section: Thermal Gravimetric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of clay with the imidazolium ILs results in a shift in the (001) peak by 0. 8 . This corresponds to an increase in d-spacing of about 0.16 nm, indicating that the surfactant molecules are intercalated into the clay galleries.…”
Section: Thermal Gravimetric Analysismentioning
confidence: 99%
“…PET/clay nanocomposites have been prepared by using in situ polymerization [3,[8][9][10], solution mixing [9,11], and melt blending [3,12,13]. Recently, a modified melt blending method was introduced in which a MMT water solution was blended with the polymer in a twin-screw extruder [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of PET nanocomposites, different results have been reported. Up to now, only a few researchers discovered that the organoclays can enhance the thermal stability of PET nanocomposites prepared by in situ polymerization or melt processing [14,15]. Broza and Schulte [16] prepared PBT-PTMO/MWCNT nanocomposites by master batch process and concluded that mixing, extruding, granulating, and injection molding seems to be a good alternative to other production methods such as in situ polycondensation.…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in polymer/montmorillonite nanocomposite because of its tremendously improved properties such as excellent mechanical properties [4][5][6], thermal stability [5][6][7][8], gas barrier [7,9], and flame retardation [6,8,9] compared with conventional composites. It is well known that there are two kinds of nanocomposites, intercalated or exfoliated, depending on the dispersion state of MMT layers in polymer matrix.…”
Section: Introductionmentioning
confidence: 99%